Socio-Demographic Determinants of Assessment and Testing Practices among School and Practicing Counselors - Osumah, Obaze Agbonluae; Osemeikhian, Edowaye; Ehigbor, B. O. (Department of Guidance and Counseling, FIP, Undiksha, 2024)
The focus of this study is the limited understanding of socio-demographic factors influencing assessment and testing practices among school counselors and other practicing counselors. This research aims to identify the socio-demographic variables that predict such practices. The study employed a quantitative approach with a survey design. The sample comprised 218 counselors selected through purposive sampling during the annual conference of a professional counseling association. Data were collected using an instrument titled “Socio-demographic Variables Predicting Assessment and Testing Practices of School and other Practicing Counsellors Scale (SVPATPSPCNS),” developed based on an in-depth literature review. Data collection was conducted by the researcher and six research assistants. Data analysis utilized multiple regression methods to identify predictive variables. The results indicate that socio-demographic variables such as qualifications, experience, location, and training significantly influence counselors' assessment and testing practices. The findings emphasize the importance of adequate qualifications, sufficient experience, and participation in training and conferences to enhance counselors' competencies in assessment and testing practices. Key recommendations include the need for counselors to obtain relevant formal education, participate in empowerment training, and continuously improve their professional competencies through conferences and advanced training programs.